Aliran informasi dalam organisasi perpustakaan - Abdul Karim Batubara (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
Building a good organization is built through interaction or communication between individuals as members. One thing that must be built is how the information can be received and disseminated properly and appropriately. Library as an unique organization of course have to have the right management in the stream information to fellow members of librarians and relevant parties in achieving the objectives of the vision and mission that has been set.